2014
DOI: 10.1094/mpmi-06-14-0184-r
|View full text |Cite
|
Sign up to set email alerts
|

Xanthomonas citri subsp. citri Type IV Pilus Is Required for Twitching Motility, Biofilm Development, and Adherence

Abstract: Bacterial type IV pili (T4P) are long, flexible surface filaments that consist of helical polymers of mostly pilin subunits. Cycles of polymerization, attachment, and depolymerization mediate several pilus-dependent bacterial behaviors, including twitching motility, surface adhesion, pathogenicity, natural transformation, escape from immune system defense mechanisms, and biofilm formation. The Xanthomonas citri subsp. citri strain 306 genome codes for a large set of genes involved in T4P biogenesis and regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
91
0
19

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(117 citation statements)
references
References 106 publications
7
91
0
19
Order By: Relevance
“…PilR belongs to the PilS-PilR TCS, which is conserved in proteobacteria and is involved in the regulation of T4P synthesis and twitching motility (17)(18)(19). This TCS also plays a role in bacterial attachment to surfaces and biofilm formation (20)(21)(22)(23).…”
Section: Resultsmentioning
confidence: 99%
“…PilR belongs to the PilS-PilR TCS, which is conserved in proteobacteria and is involved in the regulation of T4P synthesis and twitching motility (17)(18)(19). This TCS also plays a role in bacterial attachment to surfaces and biofilm formation (20)(21)(22)(23).…”
Section: Resultsmentioning
confidence: 99%
“…As described for other plant pathogenic bacteria, in planta colonization by Xtg is likely to be dependent on the type IV pilus (T4P), which mediates adherence and twitching motility [57]. A corresponding gene cluster was also identified in the other X. translucens pathovars.…”
Section: Discussionmentioning
confidence: 96%
“…However, genes coding for proteins of the T2SS general secretion pathway, as well as for proteins putatively involved in the formation of type IV pili (T4P) are present [4,54]. T4P are flexible surface filaments that are assembled through the general secretion pathway and play diverse roles, for example, in twitching motility, surface adhesion, natural transformation, biofilm formation and chemotaxis [73,74]. It has been speculated that they may provide an important function in auto-aggregation and biofilm formation for CaLas [54], but this hypothesis remains to be proved.…”
Section: Secretion Systems and Effectorsmentioning
confidence: 99%
“…In Xfa, T4P are required for obstruction of sap flow, intercellular communication, and migration of bacterial cells within the xylem [75][76][77][78]. In Xcc, it was recently shown that, like in Xfa, T4P are required for twitching motility, adhesion, and biofilm formation [74,79].…”
Section: Secretion Systems and Effectorsmentioning
confidence: 99%